Antidiabetic activity of herbal green tea extract from white mangrove (Avicennia marina) leaves towards blood glucose level of diabetic wistar rats (Rattus novergicus) - Hardoko; Binti Nafi’ah; Bambang B. Sasmito; Yuniwaty Halim (International Journal of Food Studies)
Green tea Camellia sinensis contains polyphenol that has antidiabetic activity. Mangrove leaves also contain polyphenol which potentially gives these leave antidiabetic activity. The aim of this research was to determine the ability of herbal green tea extract from white mangrove (Avicennia marina) leaves to decrease blood glucose level of diabetic Wistar rats (Rattus novergicus). The method used was experimental and involved giving a herbal green tea extract from white mangrove leaves with concentration of 100, 200 and 300 mg/200g BW/day, and positive control, i.e. glybenclamide (0.09 mg/200 g BW/day), to diabetic rats injected with Streptozotocin (STZ) and Nicotinamide (NA). The rats were observed on day 0, 5, 10 and 15. The results showed that the herbal green tea extract from white mangrove leaves decreased the blood glucose level of diabetic rats. The effective extract dose that decreased the blood glucose level of diabetic rats was 300 mg/200 g BW, which is comparable to the effect produced by glybenclamide (antidiabetic medicine). This dose could decrease the blood glucose level of diabetic rats to reach a normal blood glucose level after 20 days.